I survived the shark attacks of 1916 - Tarshis, Lauren; Dawson, Scott (New York : Scholastic, 2010)
In July, 1916, Chet Roscow is fascinated by news accounts of the great white shark said to be attacking people along the New Jersey shore not far from his home, but when he goes swimming in Matawan Creek he discovers the truth of the stories.
Keywords: Shark attacks -- Juvenile fiction; Shark attacks -- New Jersey -- Juvenile fiction; Seashore -- New Jersey -- History -- Juvenile fiction; New Jersey -- History -- 20th century -- Juvenile fiction; Shark attacks -- Fiction; Sharks -- Fiction; Seashore -- Fiction; New Jersey -- History -- 20th century -- Fiction; Adventure and adventurers -- Fiction; Survival -- Fiction; Adventure fiction